Disoriented Temporalities: Narrating postcolonial Progress(ions) in the Novels of Ngugi wa Thiong’o and Ahmadou Kourouma. - Shang, Gilbert Ndi (Advances in Social Sciences Research Journal, 2015)
Gilbert Ndi Shang Bayreuth Academy of Advanced African Studies, University of Bayreuth Email: ndishang@yahoo.co.uk Tel:004917637065255 Postal Address: Bussardweg 43, Bayreuth 95445, Bayern- Germany Abstract The African novel is one of the prescient prisms through which social, cultural and political transformations on the continent can be apprehended. As such, it is not merely a site of reflection on the society, but a pole of constructive imagination on the intricate link between the past and the present, the global and the local, the ephemeral and the enduring. In this paper, we examine artistic representations of “moments of change” and historical progression in Ngugi’s Wizard of the Crow and Kourouma’s En Attendant le Vote des Bêtes Sauvages. Through diverse narrative techniques, characterization and thematic articulations, we examine how the two novels expose the ‘disturbed movement’ of historical “progression”in the postcolony wherein the new era of hope often carries shades of the past and seeds of future disillusionment. Transitions therefore become instances where past practices are embedded and complexified in the present. However, despite the tendency towards historical determinism in the two novels whereby any moment of change is fictionalized as a repetition of history, both authors, through different artistic forms and with different intensity, expound an open-ended and equivocal future where hope is juxtaposed with despair and optimism contrasted with uncertainty.